2017
DOI: 10.1111/1753-6405.12629
|View full text |Cite
|
Sign up to set email alerts
|

Low rates of predominant breastfeeding in hospital after gestational diabetes, particularly among Indigenous women in Australia

Abstract: Objectives: To investigate rates of ‘any’ and ‘predominant’ breastfeeding in hospital among Indigenous and non‐Indigenous women with and without gestational diabetes mellitus (GDM). Methods: A retrospective study of singleton infants born from July 2007 to December 2010 at Cairns Hospital, Australia, following GDM pregnancy, using linked hospital and birth data (n=617 infants), with a subsample of medical record reviews (n=365 infants). Aggregate data were used to compare to breastfeeding rates among infants b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 36 publications
3
32
1
3
Order By: Relevance
“…In line with previous studies, we observed lower rates of predominant breastfeeding in the first two weeks after delivery in mothers with recent GDM . Our finding of an earlier cessation of predominant breastfeeding after GDM supports the findings of studies from Denmark and Spain .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies, we observed lower rates of predominant breastfeeding in the first two weeks after delivery in mothers with recent GDM . Our finding of an earlier cessation of predominant breastfeeding after GDM supports the findings of studies from Denmark and Spain .…”
Section: Discussionsupporting
confidence: 92%
“…Being breastfed has been associated with reductions in overweight or obesity and type 2 diabetes in children , although findings from studies on the children of mothers with GDM were inconsistent . Whereas studies have found lower rates of initiation of exclusive breastfeeding after GDM , country‐specific differences have been observed for the continuation of exclusive and predominant breastfeeding .…”
Section: Introductionmentioning
confidence: 99%
“…(28) Assim como as doenças infectocontagiosas, outras doenças como a hipertensão, o diabetes e a obesidade podem interferir no início e manutenção do AM, tanto pela separação do binômio devido à necessidade de internação da puérpera e/ou criança em Unidade de Terapia Intensiva, quanto pelo uso materno de medicações não compatíveis com essa prática. (9,(12)(13)(14)29) Apesar disso, as mulheres estudadas não apresentaram interferência da gestação de risco na prática do AM. Dessa forma, o suporte profissional adequado nessas situações é fundamental para prevenir o desmame ou a introdução desnecessária de fórmulas infantis.…”
Section: Discussionunclassified
“…(10,11) Assim como o excesso de peso, a Diabetes materna também parece interferir negativamente na lactação, devido a hiperinsulinemia fetal e, consequente aumento do risco de hipoglicemia neonatal, favorecendo a introdução precoce de fórmulas infantis. (12,13) Além disso, estudo americano demonstrou que 12% a mais das mulheres com Diabetes Mellitus Gestacional (DMG) relataram redução da produção láctea quando comparadas àquelas que não apresentavam tal doença. (12) As síndromes hipertensivas da gestação também têm sido associadas ao início tardio e à descontinuidade precoce da amamentação.…”
Section: Introductionunclassified
See 1 more Smart Citation